2020
DOI: 10.1101/2020.08.11.243733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Swarming bacteria undergo localized dynamic phase transition to form stress-induced biofilms

Abstract: Swarming and biofilm formation are two modes of bacterial collective behavior that enable cells to increase their tolerance to anti-microbial stressors. Swarming is a rapid type of surface colonization, and therefore its ability to withstand high antibiotic concentrations could lead to the subsequent establishment of highly resilient biofilms in regions that could not otherwise have been colonized. However, whether swarms can transit into biofilm at all, and how, remains unclear. Using Bacillus subtilis, we re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 66 publications
3
24
2
Order By: Relevance
“…[87,88] For instance, bacteria often live in biofilms with complex spatial arrangements, self-organized patterns and localized species interactions. [89,90] In gut microbiome, microbial diversity and density vary greatly along both the longitudinal and the transverse axis, largely driven by the variations of local microenvironmental properties. [91] Gut crypts and the transverse folds separate the community into spatially segregated habitats that house distinct microbes.…”
Section: Discussionmentioning
confidence: 99%
“…[87,88] For instance, bacteria often live in biofilms with complex spatial arrangements, self-organized patterns and localized species interactions. [89,90] In gut microbiome, microbial diversity and density vary greatly along both the longitudinal and the transverse axis, largely driven by the variations of local microenvironmental properties. [91] Gut crypts and the transverse folds separate the community into spatially segregated habitats that house distinct microbes.…”
Section: Discussionmentioning
confidence: 99%
“…A transition between motile and immotile cells is more typically associated with cells of multicellular organisms, such as the epithelial-mesenchymal transition (38). The active matter community has examined the cell motility and pattern formation (3941). Cells used here demonstrated a complete loss of motility, as opposed to reduced motility in regions of high cell density, suggesting the transition is not due to physical processes such as crowding and jamming.…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of aggregate formation, especially aggregates composed of immotile cells, remain unclear. Previous studies have proposed that the clustering of cells into high density aggregates and biofilms is a stress response that enables cells to survive under harsh conditions such as low availability of nutrients or exposure to toxins (41,44). Would additional benefits be conferred to aggregates of immotile cells?…”
Section: Discussionmentioning
confidence: 99%
“…Some of the collective dynamics allow swarming bacteria to better cope with environmental stress. In a recent study, we showed that swarming B. subtilis colony can undergo biofilm formation through dynamic localised phase transition, which allows swarming bacteria to overcome several forms of environmental stress such as antibiotics, UV light and spatial confinement [ 52 ]. This phase transition appeared to be compatible with a physical theory of collective motion, known as motility-induced phase separation (MIPS), where self-propelled particles (e.g.…”
Section: Cell Shape and Density Impact Bacterial Collective Behaviourmentioning
confidence: 99%